Long-term Safety Monitoring and Efficacy Status of Infliximab and its Biosimilars in Psoriasis Management - Sharma, Kiran; Ghai, Roma; Rana, Neha (Current Drug Safety, 2025)
Infliximab (INF), a murine human monoclonal antibody, is a substantially more successful biologic than topical drugs for treating mild to severe psoriasis because it clears the skin rapidly due to its fast onset of action. Loss of responsiveness over time and some adverse effects, especially the experience of infusion reactions, are the major causes of non-compliance with INF medication. Therefore, evaluation of the long-term reliability of anti-tumor necrosis factor (TNF) medications is necessary for the assessment of the risks associated with long-term anti-TNF therapy. For psoriasis, there are registered safety statistics; however, these individuals might not receive the same level of care as those in a randomized study. Few assessments of the safety of anti-TNF medications across indications, including their biosimilars, are present, but it’s still unknown how anti-infliximab antibodies arise and produce harmful effects. INF biosimilars, when subjected to human studies to reduce cost and improve access, provide therapeutic benefits with associated adverse events, showing variations in incidence depending upon varying patient populations and no new safety indications. During therapy, certain individuals develop antibodies against INF, which are believed to be linked to a loss of response (LOR). Additional research aimed at identifying individuals who are susceptible to treatment resistance is likely to assist doctors in accurately selecting the appropriate candidates for anti-TNF-α therapy and enhancing the long-term effectiveness of the treatment. From clinical studies, we expect to learn about how to utilize INF or its biosimilars more effectively in the management of psoriasis. Therefore, the paper focuses on the efficacy and safety monitoring of INF and developed biological therapies.
Keywords: psoriasis